The Me I Used to Be - Ryan, Jennifer, 1973-; Pressley, Brittany ([New York, NY] : Harper Audio, 2019)
After serving time for a crime she didnt commit, Evangeline returns home to a cold welcome. Her mother blames her for her fathers death, and her brothers want her out of their way. When Evangeline learns shes solely responsible for their failing ranch, putting her familys future squarely on her shoulders, shell have to find a creative way to save their home before they lose it all. Her only ally: the cop who sent her away. Chris Chambers is positive she went to prison to protect someone else. He strikes a deal: help him track down the real criminals in exchange for clearing her name. But the closer Evangeline and Chris get to exposing the truth, and to each other, the deeper Evangeline is drawn into a dangerous sting that could finally bring her justice, or put her dreams on hold permanently.
Keywords: Man-woman relationships -- Fiction; False imprisonment -- Fiction; Families -- Economic aspects; Fiction; Homecoming -- Fiction; Women ranchers -- Fiction; Ranches -- California; Napa Valley; Fiction; Napa Valley (Calif.) -- Fiction; Thrillers (Fiction); Romance fiction; Domestic fiction; Downloadable audiobooks; Audiobooks